As representações de estudantes de uma universidade francesa sobre as proximidades na aprendizagem de português como língua adicional - Ana Paula Andrade Duarte (2022)
In a worldwide overview where internacional partnerships, technology growth, constant changes on job market, academic mobility, migratory flows, among others, are increasingly taking place, the need to pay attention and reflect about the contact between languages and cultures is highlighted. Therefore, there's a need to put into practice a plurilingual education that sets more significant connections between the languages that already composes the linguistic repertoire of the speakers and the new languages they wish and/or need to learn (ALAS-MARTINS, 2014). Hence, the issue of proximity between sister languages is extremely relevant in the academic context, for example, precisely because courses to this audience requires special planning, due to characteristics such as high reading comprehensibility. According to Otonello (1999), factors such as learners' motivation and their relationship with the target language may be determinant for the progression of their learning. Thus, in this thesis, I aim to investigate whether representations (LASAGABASTER, 2006) of spatial, transactional, interactional, sociocultural, cognitive, and linguistic distances-proximity are considered as a brake or a lever for university students in the learning of Portuguese as an Additional Language (PLA). In view of research by authors such as Dabène (1984), Debyser (1984), Candelier (2006; 2008), Degache and Garbarino (2017), I specifically focus on Didactique des Langues, plural approaches and intercomprehension between nearby languages, checking out the representations around learning PLA. The corpus of this qualitative research is composed of 93 questionnaires filled out by speakers of nearby languages – French, Spanish and Portuguese – and 21 semi-structured interviews conducted with learners who were studying PLA at the Université Grenoble Alpes in France. Through the questionnaires, I had access to the student’s personal data, their linguistic repertoires and their representations in relation to the Portuguese language, their learning, the performance of themselves in the subjects, the ease or difficulty to learn new languages. In the interviews, I enlightened and expanded on information gathered in the questionnaires, and presented a video of an interaction between a customer and an attendant at a snack bar, recorded in Brazil, from which the students expressed their representations about the six categories of distance-proximity above mentioned. The participants' data are progressively presented, based i) on the 93 questionnaires answered by the students, ii) on looking into the 21 participants' questionnaires, iii) the analysis of the 7h46min10sec of interviews with the 21 participants, and iv) the observation of possible changes in their "starting" representations throughout the interview. In the analysis, the learners' representations of the focused distance-proximities are extracted mainly from the interview and a subtopic is devoted to detailing what was found about each category of distance-proximity in the interaction with each learner. Based on this, I conclude that, usually, and as expected, the proximities identified are seen as triggers for learning, while the distances are perceived as hindrances. However, it was curious to check that sometimes the same proximity or distance is noted as both a brake and a lever by participants in PLA learning.